Design optimization of a novel dual-skewed Halbach-array double-sided axial flux permanent magnet motor for electric vehicles - Phuson Srikhumphun; Pattasad Seangwong; Nuwantha Fernando; Apirat Siritaratiwat; Pirat Khunkitti (Scientific Reports)
Abstract This paper introduces the design and analysis of a novel dual-skewed Halbach-array permanent magnet (PM) double-sided axial flux (TORUS) motor developed for electric vehicle applications. The proposed design integrates a dual-skewing modification in the Halbach rotor PM arrangement to achieve enhanced flux focusing capability, higher torque density, and reduced torque ripple. A multi-objective genetic algorithm is employed to optimize the design. Initial validation of the improved flux-focusing is conducted using a magnetic equivalent circuit, followed electromagnetic performance evaluation employing 3D finite element analysis. Compared to a benchmark design, the proposed motor demonstrates reduced air-gap flux leakage, improved flux focusing, and superior PM utilization, resulting in a 7.8% increase in average torque, decreased torque ripple, and improved efficiency. Additionally, demagnetization analysis under transient overload conditions verifies the magnetic robustness and operational integrity of the proposed Halbach TORUS motor. Findings highlight the suitability and potential of the proposed dual-skewed Halbach-array PM configuration for further advancements in axial flux machines.